Linguistic Transculturation in Raya and The Last Dragon Movie - Harida, Ratri; Vongphachan, Phoutsavad; Putra, Tomy Kartika; Arifin, Adip (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
Southeast Asia provides a big market for “global” culture. Disney released Raya and the Last Dragon to seize the opportunity. The movie claimed itself as a Southeast Asian-inspired fantasy movie with diverse cultural images. This descriptive research involves collecting and analyzing non-numerical data from articles about Southeast Asian culture, Raya and the Last Dragon, and the movie script. This research focuses on finding the semantic-linguistic traits of transculturation within the movie. The semantic-linguistic transculturation within the movie was shown in 1) the names of the characters, 2) the use of mantra or magical chant, and 3) the use of American English informal contraction, slang, portmanteau, and compound words. Raya and the Last Dragon is a movie that shows linguistic transculturation through the use of the character’s name, words and phrases that relate to South Asian culture, mantras and magical chants, and the use of informal English contractions, slangs, portmanteaux, and compound words. The study of other linguistic transculturation levels will provide challenging goals for the other researchers.